Thermochemistry of Grenfell Tower fire disaster: catastrophic effects of water as an 'extinguisher' in aluminium conflagrations - Maguire, John F. (2021)
We review the thermochemistry of combustion reactions involved in the Grenfell Tower fire that occurred during the early hours of 14thJune 2017. London Fire Brigade (LFB), having advised all the occupants to stay in their apartments, attempted to extinguish the fire with water. The Grenfell Tower 24-storey block had recently been re-clad with an insulationto meet energy saving targets.It comprised an aluminum exterior façade, and a polymer composite thermal insulator ‘sandwich filler’, mainly polyethylene, with narrow air gaps inbetween polymer and aluminium sheets.The renovated window frames were also made of aluminum coated with a powdered polyester. Here, we highlight the scientific thermochemical reasonswhy water should never be used on aluminum fires; not least because a mixture of aluminium and water is a NASA rocket fuel! When the plastic insulation initially catches fire and burns with limited oxygen (O2 in air) to carbon(C), seen as an aerosol (black smoke) and black residue, the heat of reaction melts the aluminum(Al)and increases its fluidity and volatility, hence also its reactivity,whence it rapidly reacts with the carbon product of polymer combustion to form aluminum carbide (Al4C3). The heat of formation of Al4Cl3 is so great that it becomes white hot sparks like fireworks. At very high temperatures, both molten Al and Al4C3 aerosol react violently with water to give alumina fine dust aerosol(Al2O3)+ hydrogen (H2) gas and methane (CH4) gas, respectively, with white smoke and residues. These highly inflammable gases, with low spontaneous combustion temperatures, instantaneously react with the oxygen in air accelerating the fire out of control. Adding water to an aluminum fire is like adding “rocketfuel” to the existing flames. The timeline of events and photographic evidence corroborates this scientific explanation why a 4th-floor kitchen-appliance fire became a major tower-block inferno within 12minutes of applying water as a would-be extinguisher. A CO2-foam/powderextinguisher, as deployed in the aircraft industry against aluminum+plastic fires by smothering, might have contained the fire in its early stages. Thermochemistry of Grenfell Tower Fire Disaster